[Conferment of St. La Salle medal] - Ortiz, Justino C. (Animo Repository, 1993)
On the celebration of the Feast of Saint John Baptist de La Salle, DLSU conferred the Saint La Salle Medal on Rt. Rev. Msgr. Justino C. Ortiz, P.A.